The Evidentiary Power of an Authentic Deed Buying and Selling Land in the Digital Age - Indrati Rini (East Asian Journal of Multidisciplinary Research, 2023)
Land sale and purchase transactions are one type of agreement that is regularly carried out by members of the community. As evidence of the existence of a land sale and purchase agreement, it must be accomplished by the parties in front of an authorized official, specifically a Notary / Land Deed Official. In order to ensure legal certainty over the transfer of property rights to land, it is written in the form of an authentic deed. It is aimed for the validity of land ownership, proof of ownership of property rights is required. In practice, there are frequently cases related to land sale and purchase deeds and certificates of ownership that result in cancellation by both judicial institutions and authorized officials. In today's digital era, electronic devices can be used as a means of supporting land sale and purchase transactions that must be carried out based on the principles of accuracy and applicable law.